2003
DOI: 10.1182/blood-2002-10-3313
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic sickle mice have vascular inflammation

Abstract: Inflammation may play an essential role in vaso-occlusion in sickle cell disease. Sickle patients have high white counts and elevated levels of serum C-reactive protein (CRP), cytokines, and adhesion molecules. In addition, circulating endothelial cells, leukocytes, and platelets are activated. We examined 4 transgenic mouse models expressing human ␣-and sickle ␤-globin genes to determine if they mimic the inflammatory response seen in patients. These mouse models are designated NY-S, Berk-S Antilles , NY-S/S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
194
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(206 citation statements)
references
References 72 publications
7
194
0
5
Order By: Relevance
“…Endothelial cells (ECs) can detach from the vascular wall and circulate in the bloodstream, and would then be termed CECs. It has long been shown that the level of CECs is significantly higher in patients with widespread vascular damage, such as antineutrophil cytoplasmic antibody‐associated small vessel vasculitis (Woywodt, Streiber, et al., 2003), sickle cell crisis (Belcher et al., 2003), and pulmonary hypertension (Bull et al., 2003). Therefore, CECs have been used as a marker of endothelial damage in a variety of vascular disorders (Alessio et al., 2013; Davignon & Ganz, 2004; Dignat‐George & Sampol, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells (ECs) can detach from the vascular wall and circulate in the bloodstream, and would then be termed CECs. It has long been shown that the level of CECs is significantly higher in patients with widespread vascular damage, such as antineutrophil cytoplasmic antibody‐associated small vessel vasculitis (Woywodt, Streiber, et al., 2003), sickle cell crisis (Belcher et al., 2003), and pulmonary hypertension (Bull et al., 2003). Therefore, CECs have been used as a marker of endothelial damage in a variety of vascular disorders (Alessio et al., 2013; Davignon & Ganz, 2004; Dignat‐George & Sampol, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Upon pathological analysis, there is tissue damage in multiple organs including the kidney, liver, lung, and spleen [34][35][36]. Like human SCD patients, transgenic b S mice display numerous signs of an inflammatory response such as elevated white counts and enhanced activation of NF-kB, a transcription factor critical for the inflammatory response [37]. In addition, there are significant increases in the expression of endothelial cell adhesion molecules and the acute phase response protein serum amyloid P-component (SAP) [37].…”
Section: Introductionmentioning
confidence: 99%
“…Like human SCD patients, transgenic b S mice display numerous signs of an inflammatory response such as elevated white counts and enhanced activation of NF-kB, a transcription factor critical for the inflammatory response [37]. In addition, there are significant increases in the expression of endothelial cell adhesion molecules and the acute phase response protein serum amyloid P-component (SAP) [37]. Sickle mice exhibit biochemical footprints consistent with excessive reactive oxygen species (ROS) generation, even at ambient air [5].…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, we have unambiguously demonstrated that this TF expression mouse is triggered by the inflammatory state that is known to develop in the NY1DD mouse on exposure to H/R [6]. We believe that the documented presence of an inflammatory state in the hBERK1 mouse [8] also possibly accounts for its TF expression even at ambient air, although this has not been unambiguously proven. In any case, we had expected the hypothesis stated above to be true because a TF-modulating effect for NO has already been demonstrated in cultured endothelial cells [9,10].…”
Section: Discussionmentioning
confidence: 81%
“…This observation is relevant because human and murine sickle states are both characterized by this state [7,8]. Indeed, we regard sickle disease as comprising a paradigmatic example of ischemia/reperfusion [7].…”
Section: Introductionmentioning
confidence: 99%